PARTISIPASI MASYARAKAT DALAM PELAKSANAAN PROGRAM PEMBANGUNAN DESA SEI GOLANG KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Saptomo, Doni; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The village is a tool to achieve national development goals; the village is the leading government agency that can be reached the real target group which wantedto be empowered. In order to support the implementation of Law No. 32 of 2004 on Village Government and Law Number 25 Year 2004 concerning national development planning system, the development of which were conducted by using the paradigm of empowerment was necessary to realize community participation either in the planning, implementation or control of village construction. The objective of theresearch was to determine the community's participation in the implementation of development programs and to identify inhibiting factors of communitys’ participation in the implementation of development programs in the Village of Sei Golang Kelayang District of Indragiri Hulu Regency.The concept of the theory used the Chohen and Uphoff theory in (Dwiningrum, 2011: 61). Indicators in this study such as: Mobilizing Resources and fund, Administration and Coordination and Translation Program. While the factors that influenced the unsuccessful of participation was based on what the researcher found in the field.The results of the research could be concluded that public participation in the implementation of development programs in the Village of Sei Golang Kelayang District of Indragiri Hulu regency in less active category. In other words, there were still many problems in implementing rural development sei golang. The faktor inhibitor of community participation in the development program was the difficulty to mobilize human resources, communication and participation. These factors had an influence on public participation in the implementation of development program in Village of Sei Golang.Keywords: Participation, Development of Participatory, Mobilizing Resources and Funding, Administration and Coordination, Elaboration Program.